(untitled) (Journal of Economic Research & Business Administration, 2015)
The article reflects the current state of the state of financial market regulation in the Republic of Kazakhstan , its goals , principles and objectives . The author shares the opinion of the regulatory issues and practices , as well as opportunities for economic growth .